2017
DOI: 10.1007/s00248-017-1095-7
|View full text |Cite
|
Sign up to set email alerts
|

Prodigiosin, Violacein, and Volatile Organic Compounds Produced by Widespread Cutaneous Bacteria of Amphibians Can Inhibit Two Batrachochytrium Fungal Pathogens

Abstract: Symbiotic bacteria can produce secondary metabolites and volatile compounds that contribute to amphibian skin defense. Some of these symbionts have been used as probiotics to treat or prevent the emerging disease chytridiomycosis. We examined 20 amphibian cutaneous bacteria for the production of prodigiosin or violacein, brightly colored defense compounds that pigment the bacteria and have characteristic spectroscopic properties making them readily detectable, and evaluated the antifungal activity of these com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 61 publications
1
96
0
1
Order By: Relevance
“…Our results, along with other studies, suggest that the range of microbial species with antifungal potential is wider than previously considered [3]. Since various studies have found that some bacterial morphotypes from specific groups (e.g., Pseudomonas, Serratia) are effective inhibitors of the fungal pathogen [27,60], further research is necessary to determine if these new candidates meet the requirements to be used as probiotics. It is also key to determine the inhibition spectrum of symbiotic bacteria because antifungal capacities may differ among Bd strains [61,62].…”
Section: Discussionmentioning
confidence: 51%
“…Our results, along with other studies, suggest that the range of microbial species with antifungal potential is wider than previously considered [3]. Since various studies have found that some bacterial morphotypes from specific groups (e.g., Pseudomonas, Serratia) are effective inhibitors of the fungal pathogen [27,60], further research is necessary to determine if these new candidates meet the requirements to be used as probiotics. It is also key to determine the inhibition spectrum of symbiotic bacteria because antifungal capacities may differ among Bd strains [61,62].…”
Section: Discussionmentioning
confidence: 51%
“…In amphibians, some members of the skin microbiota can produce secondary metabolites that inhibit the growth of the fungal pathogen Bd. Examples of these antifungal metabolites are violacein (Brucker et al, 2008b ), prodigiosin (Woodhams et al, 2017 ), tryptophol (Loudon et al, 2014b ), indole-3-carboxaldehyde (I3C) (Brucker et al, 2008b ) and 2,4-diacetylphloroglucinol (2,4 DAPG) (Brucker et al, 2008a ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanisms by which some populations resist Bd could inform management strategies for threatened amphibians. can produce antifungal compounds that reduce Bd load (Brucker et al 2008, Woodhams et al 2018. Whether individual frogs survive or succumb to disease may be in part a result of the rate of their microbiome response to Bd proliferation (Jani and Briggs 2014).…”
Section: Implications For Managementmentioning
confidence: 99%
“…Strains common to amphibian skin such as Janthinobacterium lividum, Serratia spp., and Pseudomonas spp. can produce antifungal compounds that reduce Bd load (Brucker et al 2008, Woodhams et al 2018). Transplantation of J. lividum from survivors to susceptible individuals has been shown to be most effective in protecting against new Bd outbreaks when applied to the tadpole stage (Jin Song et al 2019).…”
Section: Implications For Managementmentioning
confidence: 99%